Integrated transcriptome, small RNA and degradome sequencing approaches proffer insights into chlorogenic acid biosynthesis in leafy sweet potato. - Yi Liu (PLoS ONE, 2021)
Leafy sweet potato is rich in total phenolics (TP) which play key roles in health protection, the chlorogenic acid (CGA) constitutes the major components of phenolic compounds in leafy sweet potato. Unfortunately, the mechanism of CGA biosynthesis in leafy sweet potato is unclear. To dissect the mechanisms of CGA biosynthesis, we performed transcriptome, small RNA (sRNA) and degradome sequencing of one low-CGA content and one high-CGA content genotype at two stages. A total of 2,333 common differentially expressed genes (DEGs) were identified, and the enriched DEGs were related to photosynthesis, starch and sucrose metabolism and phenylpropanoid biosynthesis. The functional genes, such as CCR, CCoAOMT and HCT in the CGA biosynthetic pathway were down-regulated, indicating that the way to lignin was altered, and two possible CGA biosynthetic routes were hypothesized. A total of 38 DE miRNAs were identified, and 1,799 targets were predicated for 38 DE miRNAs by using in silico approaches. The target genes were enriched in lignin and phenylpropanoid catabolic processes. Transcription factors (TFs) such as apetala2/ethylene response factor (AP2/ERF) and Squamosa promoter binding protein-like (SPL) predicated in silico were validated by degradome sequencing. Association analysis of the DE miRNAs and transcriptome datasets identified that miR156 family negatively targeted AP2/ERF and SPL. Six mRNAs and six miRNAs were validated by qRT-PCR, and the results showed that the expression levels of the mRNAs and miRNAs were consistent with the sequencing data. This study established comprehensive functional genomic resources for the CGA biosynthesis, and provided insights into the molecular mechanisms involving in this process. The results also enabled the first perceptions of the regulatory roles of mRNAs and miRNAs, and offered candidate genes for leafy sweet potato improvements.